Nanotechnology in the Security Systems - Bonca, Janez (Springer, 2016)
The topics discussed at the NATO Advanced Research Workshop “Nanotechnology in the Security Systems" included nanophysics, nanotechnology, nanomaterials, sensors, biosensors security systems, explosive detection. There have been many significant advances in the past two years and some entirely new directions of research are just opening up. Recent advances in nano science have demonstrated that fundamentally new physical phenomena are found when systems are reduced in size with dimensions, comparable to the fundamental microscopic length scales of the investigated material. Recent developments in nanotechnology and measurement techniques now allow experimental investigation of transport properties of nano devices. This work will be of interest to researchers working in spintronics, molecular electronics and quantum information processing.